Cardiac commitment driven by MyoD expression in pericardial stem cells - Zhao, Jianfeng; Rui, Limei; Ouyang, Weili; Hao, Yingcai; Liu, Yusong; Tang, Jianfeng; Ding, Zheheng; Teng, Zenghui; Liu, Xueqing; Zhu, Hongtao; Ding, Zhaoping (Frontiers in Cell and Developmental Biology, 2024)
Cellular therapy holds immense promise to remuscularize the damaged myocardium but is practically hindered by limited allogeneic sources of cardiac-committed cells that engraft stably in the recipient heart after transplantation. Here, we demonstrate that the pericardial tissue harbors myogenic stem cells (pSCs) that are activated in response to inflammatory signaling after myocardial infarction (MI). The pSCs derived from the MI rats (MI-pSCs) show in vivo and in vitro cardiac commitment characterized by cardiac-specific Tnnt2 expression and formation of rhythmic contraction in culture. Bulk RNA-seq analysis reveals significant upregulation of a panel of genes related to cardiac/myogenic differentiation, paracrine factors, and extracellular matrix in the activated pSCs compared to the control pSCs (Sham-pSCs). Notably, we define MyoD as a key factor that governs the process of cardiac commitment, as siRNA-mediated MyoD gene silencing results in a significant reduction of myogenic potential. Injection of the cardiac-committed cells into the infarcted rat heart leads to long-term survival and stable engraftment in the recipient myocardium. Therefore, these findings point to pericardial myogenic progenitors as an attractive candidate for cardiac cell-based therapy to remuscularize the damaged myocardium.